The Ugly Laws : Disability in Public. - Schweik, Susan M. (History of disability series., 2009)
In the late-nineteenth and early-twentieth centuries, municipallaws targeting "unsightly beggars" sprang up in cities across America. Seeming to criminalize disability and thus offering a visceral example of discrimination, these "ugly laws" have become a sort of shorthand for oppression in disability studies, law, and the arts. In this watershed study of the ugly laws, Susan M. Schweik uncovers the murky history behind the laws, situating the varied legislation in its historical context and exploring in detail what the laws meant. Illustrating how the laws join the history of the di.